Erratum: Applying a Needs Assessment Model for Improving Agricultural Education in Guinea - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Hanagriff, R., Wallace, M., & Elliot, J. (2020). Applying a Needs Assessment Model for Improving Agricultural Education in Guinea. Journal of International Agricultural and Extension Education, 27(4), 79-93” was incorrect as published. The correct DOI is: 10.5191//jiaee.2020.27479